Common Variation in NLRP3 Is Associated With Early Death and Elevated Inflammasome Biomarkers Among Advanced HIV/TB Co-infected Patients in Botswana. (11th April 2018) - Ravimohan, Shruthi; Nfanyana, Kebatshabile; Tamuhla, Neo; Tiemessen, Caroline T; Weissman, Drew; Bisson, Gregory P
Abstract: Background: Elevated inflammation is associated with early mortality among HIV/tuberculosis (TB) patients starting antiretroviral therapy (ART); however, the sources of immune activation are unclear. We hypothesized that common variation in innate immune genes contributes to excessive inflammation linked to death. As single nucleotide polymorphisms (SNPs) in inflammasome pathway genes can increase risk for inflammatory diseases, we investigated their association with early mortality among a previously described cohort of HIV/TB patients initiating ART in Botswana. Methods: We genotyped 8 SNPs within 5 inflammasome pathway genes and determined their association with death. For adjusted analyses, we used a logistic regression model. For SNPs associated with mortality, we explored their relationship with levels of systemic inflammatory markers using a linear regression model. Results: Ninety-four patients in the parent study had samples for genetic analysis. Of these, 82 (87%) were survivors and 12 (13%) died within 6 months of starting ART. In a logistic regression model, NLRP3 rs10754558 was independently associated with a 4.1-fold increased odds of death (95% confidence interval, 1.04–16.5). In adjusted linear regression models, the NLRP3 rs10754558-G allele was linked to elevated IL-18 at baseline (Beta, 0.23; SE, 0.10; P = .033) and week 4 post-ART (Beta, 0.24; SE, 0.11; P = .026). This allele was associated with increased MCP-1 at baseline (Beta, 0.24; SE, 0.10; P = .02) and IL-10 (Beta, 0.27; SE, 0.11; P = .013) at week 4 post-ART. Conclusion: The NLRP3 rs10754558-G SNP is associated with an increased risk for early mortality in HIV/TB patients initiating ART. These patients may benefit from therapies that decrease inflammasome-mediated inflammation.